Patient Satisfaction with Hemodialysis Nurses' Care: An Interaction Model of Client Behavior Perspective - Cinco, Hazel Anne R.; Rubio, Rica Rose May A. (MALATA SAINS INDONESIA, 2026)
Introduction: Hemodialysis nurses’ competence and interpersonal skills are central to patient satisfaction, yet local evidence remains limited. Objective: This study assessed patient satisfaction with nursing care in the Hemodialysis Unit of a tertiary hospital in Zamboanga City, Philippines, and examined its association with selected patient characteristics, guided by the Interaction Model of Client Health Behavior. Methods: A quantitative descriptive-correlational design was conducted among 80 randomly selected adult hemodialysis patients using an adapted Patient Satisfaction with Nursing Care Scale. Descriptive and inferential statistics were applied. Results: Overall satisfaction was high (M = 1.61, SD = 0.66), with professional-technical competence rated highest, followed by affective support and health information. Lower ratings were observed for privacy, discharge instructions, and shared decision-making. Most demographic variables were not significantly associated with satisfaction. Marital status showed positive associations across all domains, while age was positively related to decisional control and technical competence. Higher educational attainment was negatively associated with decisional control. Conclusion: Patients reported high satisfaction with hemodialysis nursing care. Improving privacy, discharge education, and shared decision-making may further enhance patient-centered care.